PENGARUH KOMPLEKSITAS PERUSAHAAN, INVESTMENT OPPORTUNITY SET, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY - Muhammad Ilyas (2023)
The aim of this research is to determine the influence of firm complexity, investment opportunity set, and firm size on Audit Delay. The population in this study consists of food and beverage companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The sample obtained for this research includes 30 financial companies selected using purposive sampling. In this study, firm complexity is measured by summing up the subsidiary companies of the parent company, the investment opportunity set is measured by dividing the net book value of fixed assets by the total book value of assets, and firm size is calculated by determining the total assets of the company using the natural logarithm scale (Ln).Hypothesis testing in this research was conducted using STATA 16 software application with a significance level of 5%. The results of the hypothesis testing indicate that firm size has a negative influence on audit delay, while firm complexity and investment opportunity set do not have a significant effect on audit delay.